THE INFLUENCE OF SLOWMATION (STUDENT-CREATED SLOW MOTION ANIMATION) ON STUDENTS' CREATIVITY AND UNDERSTANDING OF HEAT TRANSFER - Darmawanti, Hanifah Putri (2017)
The blast in personal digital technologies occurs throughout the world including Indonesia offers rising up opportunities to create digital media including for education, the creativity and conceptual understanding must be involved along with it. Therefore, this research is aimed to investigate the influence of Slowmation (Student-created Slow Motion Animation) on students' creativity and understanding of heat transfer. The research used pre-experimental one group pretest-post-test design. The sample was taken by convenience sampling technique in experimental class (n=20) with the population of 8th grade students at independence secondary school in Bandung. Students' understanding result was obtained through objective test with the result of normalized gain of 0.30 (0.70 > <g> ≥ 0.30) as medium improvement and the result of non-parametric Wilcoxon test with significant of 0.001 that means the significant difference before and after the implementation of Slowmation is exist. Meanwhile students' creativity gained through creativity process and product of Slowmation with 78.2 as above standard category. Therefore, the implementation of Slowmation (Student-created Slow Motion Animation) as learning strategy specifically on heat transfer topic influences students' creativity and understanding.